Languages As The Medium Of Instruction, A Setback Of Students’ Access Towards Higher Education: A Case Study From Rural Areas Of Pakistan - Sajad Ahmad Qaisrani; Muhammad Ramzan (Indonesian Journal of Basic Education, 2022)
The study intends to explore the difficulties of students’ access towards higher education through English language as a medium of instruction in Pakistan. Data were collected by analyzing different documents, articles, research reports, research based books, and experts opinions, teachers of English Language and a questionnaire for students. The result show that although students faces multiple problems in access towards higher education but medium of instruction in this regard is one of the main problems of students failure towards higher education. In addition in English language proficiency the students of other language then English have less achievement scores as compared to native English speakers. The study further clears that English is a dominant language as a medium of instruction at all level of Education in Pakistan. The study suggested further research to address the issue